Bimbingan Konseling Pada Anak Usia Dini Di Tk Al-Ikhlasiyah - Fauziah Nasution; Sarah Rizki Aulia; Rama Yuspika Sari; Najwa Rahmi (Peneliti.net, 2023)
This study aims to explore and analyze the effectiveness of counseling guidance in early childhood at Al-Ikhlasiyah Kindergarten using qualitative research methods. Qualitative methods are used to understand children's experiences in receiving counseling and guidance and its impact on their development in various aspects, such as social, emotional, and academic. In this study, data were obtained through several research techniques, including in-depth interviews with children, parents, and teachers at Al-Ikhlasiyah Kindergarten. In-depth interviews provided an opportunity for research participants to explain in detail their experiences and perceptions of guidance counseling. In addition to in-depth interviews, observation was also used to directly observe children's interactions and behavior in the context of learning and social interaction in kindergarten. This observation helps researchers gain deeper insight into how counseling influences children in their daily lives. In addition, document analysis was also carried out to collect additional information, such as records of child development, reports on counseling activities, and learning materials related to counseling guidance. Analysis of this document provides a more comprehensive understanding of the implementation of counseling guidance in Al-Ikhlasiyah Kindergarten. Research participants consisted of early childhood, parents, and teachers at Al-Ikhlasiyah Kindergarten. By involving various parties involved in the child's education process, this research can provide a holistic perspective on the effectiveness of counseling in early childhood. Through the use of qualitative methods and involving a variety of participants, this research is expected to provide an in-depth understanding of the impact of counseling on early childhood development. The results of this research can be the basis for the development of a more effective guidance and counseling program in Al-Ikhlasiyah Kindergarten and other educational institutions